Micro Preemie with the Earliest Gestational Age and the Lowest Birth Weight that Survived in ICU, Dhaka Shishu (Children) Hospital, Bangladesh - Hoque, Md Shafiul; Rahman, Mobashshera; Hussain, Manzoor; Ahmed, SM Nawshad Uddin (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Prematurity is a common neonatal problem in developing countries and is associated with high mortality and both immediate and long-term morbidities. More a baby is premature more is the chance of mortality. With the advent of modern supportive care favorable outcome has been observed in extremely premature babies in developed countries, but the outcome is not satisfactory in developing countries. Recently, an incredibly low birth weight (456 grams) micro preemie was successfully managed in Dhaka Shishu Hospital. With round the clock care at the hospitals Neonatal Intensive Care Unit she was tipping the scales and discharged at the age of three months, weighing 1128 grams. To the best of our knowledge, this is the lowest birth weight baby survived in our country, an exceptional achievement and a milestone in newborn care in Bangladesh. J Bangladesh Coll Phys Surg 2017; 35(3): 142-146